Photocatalytic Activity of Zero-Valent Iron Nanoparticles Highly Dispersed on Porous Carbon Materials - Liang, Dan; Fan, Yanfei; Yue, Taixing; Wang, Wen; Shang, Qiaoyan; Chen, Ping; Zhu, Minghui; Liu, Yan; Cui, Guanwei; Tang, Bo (Frontiers in Environmental Chemistry, 2022)
During the traditional homogeneous Fenton reaction process for water treatment, the consumption rate constant of Fe2+ is much greater than its regeneration rate constant, which makes Fe2+ an almost stoichiometric loss and produces iron sludge waste. In this article, highly dispersed zero-valent Fe nanoparticles loaded on porous carbon materials (Fe-EMC) were synthesized by a one-step calcination method using Flammulina velutipes natural carbon source and Fe(NO3)3 as raw materials to solve the aforementioned problem. The as-prepared Fe-EMC materials are characterized by X-ray diffraction analysis, scanning electron microscopy, electron probe microanalyzer, high-resolution transmission electron microscopy, X-ray photoelectron spectroscopy, and N2 adsorption–desorption measurements. It exhibits excellent photocatalytic activity for the degradation of methylene blue (MB) dyes under a broad pH region. Under conditions of 0.3 g/L Fe-EMC, 0.2 M/L H2O2, pH 7.0–11.0, and 50 mg/L MB, 97.98% of the MB dyes in the solution were completely degraded within 1 h. It was attributed to the efficient regeneration cycle between Fe2+ and Fe3+ in the Fenton-like system with light irradiation, which can promote the generation of active oxygen species.